(3CSGSjGJ GdQjGVI ddJLGQjjf (B((3c(B1) ((3L(B1) /s - (3GdefUhQj(B;(3UObj(B;(3TGcQ, Ydj CMeO(B;(3MSfjf, eYhV MSf(B;(3UGHQ, eMeO ZGRj, eMeO Jhajb(B;(3eMeO UdGM GdOjfs ((3GdbGgQI(B: s (3cdjI GdJLGQI(B, s, 1993)
(3GdJHGOjd h GdJhGajb, fXQjI PGJ GdMOjf, GdeJhGdjGJ GdYOOjI h GdgfOSjI, GdeMOOGJ, GdeUahaGJ, Md GdeYGOdGJ HGdeUahaGJ, GdGMJeGd h GdMGOK, GdeHGOF GdCSGSjI dMSGH GdGMJeGdGJ, JhRjY KfGFj GdMOjf, GSJNOGe GdGMJeGdGJ aj GdYedjGJ GdJLGQjI, GSJNOGe GdGMJeGdGJ aj eQGbHI LhOI GdGfJGL, GdOhGd h GdfgGjGJ, GdJaGVd hGdJcGed, GdHQGeL GdNWjI(B-(3eaGgje CSGSjI, WQb hCSGdjH Md GdHQGeL GdNWjI, GdWQjbI GdYGeI dMd eTGcd GdHQGeL GdNWjIs
Keywords: (3GdJHGOjd h GdJhGajbs; (3GdeUahaGJs; (3YehejGJ GdQjGVjGJs